Numerical Study of Three Split-Hopkinson Shear Bar Techniques - Faizah (NIM : 13113143), Iffah
Split-Hopkinson Shear Bar Testing is a modification of the high rate-impact test of Split-Hopkinson Pressure Bar. SHSB is now growing with a variety of techniques that are hat-shaped, double-notch, and punch. However, these three techniques have different characteristics although using the same test specimen material. The main objective of this study is to determine the best and optimal SHSB technique in determining shear stress-shear strain of a material by numerical analysis of finite element method using Abaqus / CAEÃ‚Â® software. The finite element modeling is made up of a quarter solid 3D component for hat-shaped and punch techniques, as well as 3D solid half-sections for double-notch techniques. Used striker bar along 300 mm with an initial speed of 10.915 m / s, incident bar 1200 mm, and transmitted bar 1200 mm, with maraging steel material. For the specimen used material T351-2024 Aluminum (AISI Grade 16Ni) and constitutive material model Johnson-Cook. All three test techniques have differences in specimen shape, incident bar, and transmitted bar dimensions. Based on the numerical simulation results, the maximum shear stress of the hat-shaped technique is 247,66 MPa, the final shear strain 64%, and the strain rate 5162 s-1, the punch technique (τ = 181.3 MPa, γ = 34 %, γ = 5239 s-1), and double-notch technique (τ = 250,5 MPa, γ = 69%, γ = 5470 s-1). The double-notch technique was chosen as the most optimal SHSB technique because it has a slope of strain rate about 4.06 and a force error reach 0%.